Mucopolysaccharidoses in Tunisia: a molecular portrait of allelic heterogeneity and consanguinity - Coutinho, Maria Francisca (2016)
There are 11 different enzymes involved in the stepwise degradation of glycosaminoglycans (GAGs). Deficiencies in each of those enzymes result in eight different Mucopolysaccharidoses (MPSs), all sharing a series of clinical features, though in variable degrees. Typical symptoms include organomegally, dysostosys multiplex and coarse facies. CNS, hearing, vision and cardiovascular function may also be compromised. Traditionally, MPSs are recognized through analysis of urinary GAGs. Still, initial screenings of urinary GAGs allow discrimination between broad classes of MPSs but cannot distinguish subgroups. In fact, a definitive diagnosis may only be accessed through a combination of enzymatic assays and molecular analyses. Currently, there are countless laboratories in Europe where those biochemical and genetic tests are carried out. Nevertheless, developing countries often lack the necessary resources/expertise for proper diagnosis of rare genetic diseases. Being one of the labs where molecular genetic testing for virtually all MPSs is available for research purposes, we receive several samples from other countries, whose clinicians and/or centers struggle to get a molecular characterization of affected individuals. Here we present our results on the molecular characterization of MPS patients we have been receiving from Tunisia. Nine families suffering from five different diseases were studied so far: 3 MPS II; 2 MPS IIIA; 2 MPS IIIB; 1 MPS IIIC and 1 MPS VI. We have identified 9 different mutations, 5 of which were novel: 1 in the IDS gene (c.1333delC); another in the SGSH gene (p.D477N); 2 in the NAGLU gene (p.L550P and p.E153X) and yet another in the ARSB gene (p.L82P). All detected mutations were further analyzed with the most suitable approaches. Special attention was paid to the novel alterations, particularly to the missense ones, whose impact on protein structure and function was evaluated in silico. In general, there was a strong correlation between the observed clinical phenotype and the genotype assessed through molecular analysis. Also noteworthy is the astonishing level of homozygosity in our sample (100%), with each family presenting its own molecular defect, a pattern consistent with the occurrence of consanguineous matings in Tunisia, where such marriages are thought to provide social, economic and cultural benefits. Altogether, our results provide a preliminary overview of the molecular basis, enzymatic defects and clinical manifestations of MPSs in Tunisia, further supporting previous reports on the high impact of inbreeding and regional endogamy on the occurrence of autosomal recessive disorders in that country. Hopefully, these results will not only contribute to improve genetic counseling for affected families, but also to highlight the need for reinforced and continuous information of general public and health professionals on the potential negative medical impact of intra-family marriages, particularly in Northern Africa, Middle East and South Asia.